2018
DOI: 10.2298/jsc180529063s
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the knowledge of the chemical composition, biological activities and activity concentration of 40K, 137Cs, 226Ra and 232Th of the lichen Evernia prunastri

Abstract: This study reports the effect of an acetone extract of Evernia prunastri on the micronucleus distribution of human lymphocytes and effect on cholinesterase activity. Furthermore, the antioxidant activity (estimated via DPPH, ABTS, TRP and CUPRAC assays), as well as total phenolic compounds (TPC) and antibacterial activity (against two Gram-positive and three Gram-negative bacteria) were determined. Chemical profiling of four E. prunastri extracts (acetone, diethyl ether, ethyl acetate and dichloromethane) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Our previous studies showed that the cupric-reducing capacity of Ramalina capitata, Umbilicaria crustulosa, Peltigera horizontalis, Hypogymnia tubulosa and Evernia prunastri acetone extracts were 6.11, 19.76, 9.94, 46.47 and 20.75 µg TE/mg dry extract, respectively. [34][35][36][37][38] Result obtained in the current study was very near to U. crustulosa and E. prunastri effect but much lower activity than H. tubulosa.…”
Section: Tpc and Antioxidant Activitysupporting
confidence: 52%
See 4 more Smart Citations
“…Our previous studies showed that the cupric-reducing capacity of Ramalina capitata, Umbilicaria crustulosa, Peltigera horizontalis, Hypogymnia tubulosa and Evernia prunastri acetone extracts were 6.11, 19.76, 9.94, 46.47 and 20.75 µg TE/mg dry extract, respectively. [34][35][36][37][38] Result obtained in the current study was very near to U. crustulosa and E. prunastri effect but much lower activity than H. tubulosa.…”
Section: Tpc and Antioxidant Activitysupporting
confidence: 52%
“…It seems that the optimal concentration of the extract for reducing the number of MN is 2.0 μg/mL, which is in agreement with the published results of other lichen species. 34-38…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations